Comparison between Competent and Basic English Language Learners Using Cognitive and Affective Learning Strategies - Ahmad Khair, Amali (2007)
This study was carried out mainly to examine the disparity of achievement between the excellent and below the average students in relation to their cognitive and affective application in their learning styles. The study focused on whether or not the application of CCTS (Critical and Creative Thinking Skills) or TS (Thinking skills) in their learning strategies is significant. Therefore, a two-fold (quantitative and qualitative method) quasi-experimental one group pretest posttest type of study was conducted to investigate the phenomenon. This study consists of three methods of data collection; responses from the questionnaire, taped recording responses from the interviews and the analysis of the transcribed lessons conducted. A comparative study between two types of respondents are involved in this study; namely the excellent and below the average students using English as a second language thus 129 students of B(Ed.) TESL in UPM were being partially experimented on. The subjects were required to respond to the five section questionnaire of forty nine (49) items which included section A – Student’s profile and Habitual Tasks, section B – Parents’ or Guardian’s Background, section C – What a Good Learner Can Teach Us (a perception of excellent students on how to excel), section D (i) and (ii) – COGAFF and section E – Multiple Intelligence Inventory; for the quantitative part of the study. Analyses of the quantitative data were carried out using SPSS Version 13.0. The qualitative aspect of the study was basically based on the interview on how they learnt English, their experience in the process of learning the language and their strategies on how to excel in learning the target language. The transcriptions of the two lessons were provided in this study to show that the application of CCTS can either be in an ‘overt’ or direct kind of intervention or in a ‘covert’ or subtle manner of teaching as well. This was shown in the consolidation section when the researcher added another six (6) excellent students from the Al Bukhary Complex as she found that the initial part of the study proved to be insufficient in providing data of the excellent students. Therefore, the total number of respondents involved in this study was 135 students. From the descriptive analyses of the data it was discovered that the two groups of students exhibit differences in their habitual tasks and these differences can be narrowed through intervention. From the analyses of paired samples t tests and independent samples t tests of SPSS Version 13.0 it was discovered that the two groups of students also exhibit significant differences in their perception of what good learners can teach them in terms of strategies and learning styles; in their strategies and learning styles based on their cognitive and affective domains; and also in their thinking skills, all of which can be narrowed using intervention